Effects of a feed additive blend on broilers challenged with heat stress. Issue 6 (2nd November 2019) - Santos, Regiane R.; Awati, Ajay; Roubos-van den Hil, Petra J.; van Kempen, Theo A. T. G.; Tersteeg-Zijderveld, Monique H. G.; Koolmees, Peter A.; Smits, Coen; Fink-Gremmels, Johanna
ABSTRACT: We evaluated a blend of medium-chain fatty acids (MCFA), organic acids, and a polyphenol antioxidant on gut integrity. Eighty Ross Broilers were exposed to 20–22°C (control – normothermic) or to 35–39.5°C (heat stress) for eight hours a day for a period of 1 or 5 days. Birds were fed a standard diet, or a diet supplemented with the test blend. Thereafter, birds were euthanized, and intestinal sections were excised for morphological, morphometric and gene expression analyses. Blood samples were collected for glucose-6-phosphate dehydrogenase (G6PD), glutathione peroxidase (GSH-Px) activity and trolox equivalent antioxidant capacity (TEAC) determination. Heart and liver tissues were used to quantify the expression of heat shock proteins 60 and 70 (HSP60 and HSP70, respectively) and inhibitor of kappa light chain gene enhancer in B cells alpha (IKBA). The jejunum was the most sensitive intestinal section, where heat stress modulated the expression of HSP70, of the inflammatory markers IKBA, interleukin 8 (IL-8), interferon gamma (IFNγ), and toll-like receptor 4 (TLR4). Moreover, expression of tight junctions (CLDN1, ZO1 and ZO2) and nutrient transporters (PEPT1 and EAAT3) was modulated especially in the jejunum. In conclusion, the feed additive blend protected intestines during heat stress from the decrease in villus height and crypt depth, and from the increase in villus width. Especially in the jejunum, heat stress played an important role by modulating oxidative stress and inflammation, impairing gut integrity and nutrient transport, and such deleterious effects were alleviated by the feed additive blend. RESEARCH HIGHLIGHTS Jejunum is the most sensitive intestinal segment during heat stress. Heat stress affects the expression of tight junctions and nutrient transporters. Feed management helps to alleviate the disturbances caused by heat stress. A blend of MCFA, organic acids and a polyphenol protects broilers under heat stress.